Rehabilitating an Ocular Defect with a Custom Made Ocular Prosthesis: A Clinical Report - Sreeprada Dash; Gunjan Srivastava; Gopal Krishna Choudhury (Institute of Medico-legal Publications Pvt Ltd, 2021)
An ocular prosthesis is a replacement of the ocular part of the eye in patients due to trauma, benign ormalignant lesion or congenital anomaly, there is the loss of the eye. Prosthetic rehabilitation with a customizedocular prosthesis that is proportioned and similar in appearance to that of the contralateral natural eye isneeded. This maintains the volume of the orbital socket and also helps create an illusion of the presence ofa healthy eye. It provides the individual confidence to adapt to a normal lifestyle and prevent them fromgoing into psychological distress. Various techniques have been advocated for the fabrication of the ocularprosthesis comprising the use of the stock prosthesis, custom made prosthesis and micro-implants for therehabilitation of the ocular part of the eye. A cosmetically approvable and pleasing ocular prosthesis arethose which reproduces the colour, appearance and orientation of the iris to that of the contralateral naturaleye. This clinical report describes a simple, economical and time-saving method for the fabrication of thecustomised ocular prosthesis in a patient with the ocular defect.